Taking the Pulse of Protein Interactions by EPR Spectroscopy - Cafiso, David S. (The Biophysical Society, 2012)
An article by Gaffney et al. in this issue establishes a method using pulse electron paramagnetic resonance spectroscopy to determine the location of protein substrates or binding partners with high precision.